新加坡福建会馆：文化传承之途径 = Singapore Hokkien Huay Kuan: the journey of cultural inheritance - 黄恩琪 Ng, En Qi (Nanyang Technological University, 2023)
在新加坡的历史长河中，华人社团一直扮演着积极的社会角色，不仅帮助本族群的发展，甚至也为各个种族、语言和宗教的人们在教育、医疗、公益事业和文化传承方面做出了诸多贡献。自1840年以来，新加坡福建会馆作为本地主要的华人宗乡社团之一，历经近两个世纪而始终保持着其特色和初心。福建会馆秉承服务国家、社会和族群的理念，与新加坡一同成长。作为新加坡华社最活跃的社团之一，福建会馆积极策划多项大型社群活动，如福建美食节、文化节、文化演出以及义走等，让国人深入地理解福建会馆的历史与福建华人的奋斗历程。同时，这些活动也帮助国人了解本地华社，从而让国人对新加坡的整体历史拥有更全面的认识。 然而，随着新冠病毒疫情在全球肆虐，全国所有大型活动都受到了防疫措施的限制，福建会馆及其他华社华团筹备的各项公众活动也遭受影响。面对空前巨大的挑战，福建会馆并没有退缩；而是另辟蹊径，以创新的方式重新建立起社团与社群之间的文化交流。这不仅确保了文化意识的持续传承，也体现了福建人敢于面对和克服挑战、不屈不挠和勇于拼搏的奋斗精神。Throughout the long history of Singapore, Chinese community groups have played an active social role, not only helping to develop their own ethnic groups, but also making significant contributions to education, healthcare, public welfare, and cultural heritage for people of all races, languages, and religions. Among them, the Singapore Hokkien Huay Kuan (SHHK), as one of the major Chinese clan associations in Singapore, has maintained its distinctive character and original aspirations since its establishment in 1840, spanning nearly two centuries. Adhering to the concept of serving the country, society, and ethnic groups, the SHHK has grown together with Singapore. As one of the most dynamic Chinese community groups in Singapore, the SHHK actively plans various large-scale community activities, such as Hokkien food festivals, cultural festivals, cultural performances, and charity walks, allowing people to gain deeper knowledge of the history of the SHHK, as well as the struggles of the Hokkien Chinese. At the same time, these activities also help Singaporeans to understand the local Chinese community, thus gaining a more in-depth and comprehensive perception of Singapore's overall history. However, with the global spread of the COVID-19 pandemic, all large-scale events in the country have been restricted by epidemic prevention and control measures, and several public activities planned by the SHHK and other Chinese community groups have also been affected. Faced with unprecedented challenges, the SHHK did not concede defeat, but instead found new ways to re-establish cultural exchanges between the association and the community through various innovative approaches. This not only ensures the continuous inheritance of cultural awareness but also embodies the fighting spirit of Hokkiens who are willing to face and overcome challenges, persevere, and strive for success.